Preparation of Ca/Al-Layered Double Hydroxides/Biochar Composite with High Adsorption Capacity and Selectivity toward Cationic Dyes in Aqueous - Risfidian Mohadi; Neza Rahayu Palapa; Aldes Lesbani (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
Widely reports have evaluated the use of biochar (BC) composites to layered double hydroxide (LDH) to adsorb dyes from wastewater. However, its applicability for adsorbing a mixture of cationic dyes such as Malachite green (MG), Rodhamine-B (Rh-B), and Methylene blue (MB), which causes carcinogenic and mutagenic effects on aquatic life, has not been studied. In this work, we compared the performance of CaAl-LDH/BC adsorbent with or without the addition of BC in the adsorption of cationic dyes. The adsorption study was prepared in a batch system using various temperatures, concentrations, and also contact time. The results of the characterization of Ca/Al-Biochar composite showed the unique diffraction of XRD pattern, and also showed two characteristics of starting materials. Surface area analysis by BET method showed Ca/Al-Biochar composite has a higher surface area than starting material. The results of the adsorption study of MG showed that Ca/Al-Biochar follows the pseudo-second-order kinetic model. The adsorption capacity of MG on Ca/Al-Biochar was up to 71.429 mg/g and shows selectivity toward MG in an aqueous solution. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).